Paradoxes of Nostalgia : Cold War Triumphalism and Global Disorder Since 1989. - Von Eschen, Penny M. (Durham : Duke University Press, 2022)
Penny M. Von Eschen offers a sweeping examination of the afterlife of the cold war and its lingering shadows, showing how a nostalgia and longing for stability fuels US-led militarism and the rise of xenophobic right-wing nationalism and authoritarianism around the world.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books